The Bothnian Sea ice stream: early Holocene retreat dynamics of the south‐central Fennoscandian Ice Sheet. (10th December 2016) - Greenwood, Sarah L.; Clason, Caroline C.; Nyberg, Johan; Jakobsson, Martin; Holmlund, Per
Abstract : The Gulf of Bothnia hosted a variety of palaeo‐glaciodynamic environments throughout the growth and decay of the last Fennoscandian Ice Sheet, from the main ice‐sheet divide to a major corridor of marine‐ and lacustrine‐based deglaciation. Ice streaming through the Bothnian and Baltic basins has been widely assumed, and the damming and drainage of the huge proglacial Baltic Ice Lake has been implicated in major regional and hemispheric climate changes. However, the dynamics of palaeo‐ice flow and retreat in this large marine sector have until now been inferred only indirectly, from terrestrial, peripheral evidence. Recent acquisition of high‐resolution multibeam bathymetry opens these basins up, for the first time, to direct investigation of their glacial footprint and palaeo‐ice sheet behaviour. Here we report on a rich glacial landform record: in particular, a palaeo‐ice stream pathway, abundant traces of high subglacial meltwater volumes, and widespread basal crevasse squeeze ridges. The Bothnian Sea ice stream is a narrow flow corridor that was directed southward through the basin to a terminal zone in the south‐central Bothnian Sea. It was activated after initial margin retreat across the Åland sill and into the Bothnian basin, and the exclusive association of the ice‐stream pathway with crevasse squeeze ridges leads us to interpret a short‐lived stream event, under high extension, followed by rapid crevasse‐triggered break‐up. We link this event with a c . 150‐year ice‐rafted debris signal in peripheral varved records, at c . 10.67 cal. ka BP. Furthermore, the extensive glacifluvial system throughout the Bothnian Sea calls for considerable input of surface meltwater. We interpret strongly atmospherically driven retreat of this marine‐based ice‐sheet sector.